2006
DOI: 10.1001/.399
|View full text |Cite
|
Sign up to set email alerts
|

Esterified Estrogen and Conjugated Equine Estrogen and the Risk of Incident Myocardial Infarction and Stroke

Abstract: Background: Clinical trials of conjugated equine estrogen (CEE) or estradiol vs placebo in postmenopausal women have found no effect or an elevated risk of myocardial infarction (MI) and stroke. The association of these end points with the use of esterified estrogen (EE) is unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…21-27 We previously described the comparative safety of oral esterified estrogen compared with oral CEE and found that compared with oral esterified estrogen, oral CEE was associated with an increased risk of VT and possibly MI and ischemic stroke; findings were validated in controls, where oral CEE users had greater resistance to APC than oral esterified estrogen users. 3, 4, 28 Further, recent publications suggest that estrogen and progestogen drug type may be differentially associated with cardiovascular event risk although primary analyses compared HT use with non-use. 26, 27 …”
Section: Discussionmentioning
confidence: 99%
“…21-27 We previously described the comparative safety of oral esterified estrogen compared with oral CEE and found that compared with oral esterified estrogen, oral CEE was associated with an increased risk of VT and possibly MI and ischemic stroke; findings were validated in controls, where oral CEE users had greater resistance to APC than oral esterified estrogen users. 3, 4, 28 Further, recent publications suggest that estrogen and progestogen drug type may be differentially associated with cardiovascular event risk although primary analyses compared HT use with non-use. 26, 27 …”
Section: Discussionmentioning
confidence: 99%
“…Post-MW treated with esterified estrogen alone have lower risk of ischemic stroke and myocardial infarction, and no increase in venous thrombosis risk compared to Post-MW treated with CEE [117, 141]. Also, experimental studies demonstrated that treatment of ovariectomized hypertensive rats with estradiol valerate causes an increase in serum vascular endothelial growth factor (VEGF), which accelerates endothelial cell growth both in vitro and in vivo [142].…”
Section: Introductionmentioning
confidence: 99%
“…23 A meta-analysis of nine cohort studies published in 2002 also points toward a significant increase in ischaemic but not haemorrhagic stroke with MHT ever-use compared with never-use. 24 Of the largest recent observational studies evaluating the risk of stroke in relation to MHT use, three are concordant with these conclusions, [25][26][27] whereas both Lemaitre et al 29 and Prentice et al 28 found no evidence of an elevation in the risk of stroke with MHT use.…”
Section: Cerebrovascular Diseasementioning
confidence: 75%